Deversity of vascular plants in the floodplain vegetation of Trang River Basin, Trand Province, Peninsular Thailand - Ponlawat Pattarakulpisutti (Prince of Songkla University, 2013)
Thesis (M.Sc., Botany)--Prince of Songkla University, 2011